Onde a gente se encontra!?: Espacialidades e performances mediante o mecanismo de georreferência do Instagram, caso Catu - Costa, Elivelton de Jesus (2024)
Network communication processes establish a performative context with several developments, among them, reverberations in self-presentation mechanisms. This is because technological innovations, especially those in communication and information, affect forms of sociability, languages and cognition, resulting in new ways of acting. Taking social media as places of selfpresentation of social actors in everyday life, this study aims to understand how, based on performances carried out on profiles belonging to the Instagram platform, georeferenced in Catu (BA), social actors formulate the idea of place, recording their history, from the perspective of those who are part of the platform in question. It points us to the lived space. The research takes a qualitative-quantitative approach, as a methodological procedure for data collection, using observation and selection of posts, displayed on profiles with the spatiotemporal cut of Catu from January to April 2023. It was observed, in this way, that social actors not only document their presence in Catu, but also create a mosaic of meanings that permeate the social and cultural life of the digital community. Through this interaction, social actors not only reaffirm their connection with the place, but also actively influence the construction of collective and individual identities.